Literature Review: The Effect Of Lemon Aromatherapy On Emesis Gravidarum - Rini Sulistyowati (Green Publisher Indonesia, 2021)
Nausea and vomiting (Emesis Gravidarum) often occurs in 1st trimester pregnant women. The cause is due to an increase in the hormones estrogen and HCG in early pregnancy. One of the effects is dehydration which causes the fetus to experience problems, therefore therapy is needed one of the therapies to deal with is the aroma therapy of lemon. International literature searched by electronic means with key words (emesis, lemon therapy, aromatherapy). 8 selection articles on the effect of lemon aromatherapy on emesis gravidarum. Result of this study is there were differences in emesis gravidarum in aromatherapy with the same treatment. One of the treatments for emesis gravidarum is a non-pharmacological method, namely lemon aromatherapy. Aromatherapy lemon therapy contains 66-80% limonene, geranil acetate, nerol, linalyl acetate, 0.4-15% pinene, 1-4% pinene, 6-14% terpinene and myrcen. Chemical compounds such as geranil acetate, nerol are useful for antidepressants, nantiseptics, anti spasmodics to relieve feelings of anxiety, stress, and fatigue. Conclusion of this research that the use of lemon aromatherapy is effective in reducing the occurrence of emesis gravidarum